Clinical Subtypes and Prognostic Outcomes of Rhabdomyolysis in ICU Patients - Xu, Shan; Qin, Kaixiu; Zhang, Dan (International journal of clinical practice (Esher), 2025)
Background: Rhabdomyolysis (RM) is a severe clinical syndrome with substantial heterogeneity that involves the rapid dissolution of skeletal muscles. The condition has a high prevalence and poor prognosis, particularly in critically ill patients. Subtypes of RM in critically ill patients have not been investigated. Objective: The study aimed to link the clinical RM heterogeneity with distinct prognoses and associated characteristics among different subtypes using an unsupervised analysis. Methods: Patients diagnosed with RM in the intensive care unit (ICU) from the Medical Information Mart for Intensive Care‐IV (MIMIC‐IV) database and the eICU Collaborative Research Database (eICU) were retrospectively enrolled. K‐means clustering, guided by correlation coefficients and expert opinions in intensive care medicine, was applied to identify distinct RM clinical subtypes using routinely available parameters from the first 24 h after patient ICU admission. The primary endpoint was 28‐day mortality. We assessed associations between subtypes and 28‐day mortality, as well as between treatments and 28‐day mortality in the derived subtypes, using multivariate Cox proportional hazards regression. The eICU database patients served as an external validation set. The SHapley Additive exPlanations (SHAPs) were used to visualize features of each clinical subtype. Results: A total of 2269 eligible subjects were extracted from the MIMIC‐IV. Two distinct subtypes were identified (A and B) using 17 readily available clinical and biological variables. Patients assigned to Subtype A ( n = 511) had a higher 28‐day mortality. The proportion of organ support, comorbidity index, SAPS II, and SOFA scores were all significantly higher in the Subtype A group than in the Subtype B group ( n = 1836). After adjusting for relevant covariates, Subtype A patients were independently associated with increased 28‐day mortality (HR [95% CI] = 1.70 [1.36–2.11], p < 0.001). These findings were further validated using an external cohort from the eICU dataset. Notably, Subtype A patients showed a higher mortality risk associated with sodium bicarbonate use (HR [95% CI] 1.62 [1.20–2.19], p = 0.002). Conclusions: We identified two subtypes with distinct clinical features and outcomes. Subtype A is independently associated with poor outcomes and shows increased mortality risk with sodium bicarbonate use. These findings may help clinicians better distinguish prognoses and treatment responses among RM patients.